Strategi Desain Produk Komunitas Berbasis Ekonomi Sirkular: Pengembangan Sistem Amenitas di Desa Wisata Tembi, Bantul - Nasywa Bintang Azalia; Rahmawan D Prasetya; Sekar Adita (SPACEPRO: Product Design Jurnal, 2026)
Tembi Tourism Village has skilled local artisans who work with natural fibers and other local materials. However, their products are still largely produced as white-label goods and have not been systematically integrated into the village tourism-service ecosystem. This study aims to formulate a community-based product design strategy for homestay amenities by connecting local craft production, tourism services, and circular-economy principles. The research used an exploratory qualitative approach supported by field observation, semi-structured interviews, focus group discussion, documentation, thematic analysis, and SWOT analysis. Participants included tourism managers, homestay owners, local artisans, community representatives, and design facilitators selected through purposive sampling. The findings show that local production and tourism services in Tembi still operate separately, causing community products to remain peripheral to the tourist experience. The proposed strategy is to develop amenity products such as toiletry containers, room slippers, and coasters using local materials and collaborative production mechanisms. These products can strengthen the visual identity of homestays, create a more authentic visitor experience, and keep economic circulation within the village through local production, local use, and local reinvestment. The contribution of this study lies in positioning community products not merely as souvenirs, but as functional service components within a Community-Based Tourism ecosystem.